Novel insights into causal associations of body mass index or height with pneumothorax: a two-sample Mendelian randomization study - Liu, Gengqiu; Yan, Dongqing; Wang, Xiaohuai; Liu, Anbang; Zhang, Junhang (Frontiers in Nutrition, 2024)
Background Observational studies have reported an association between body mass index (BMI) as well as height and the risk of pneumothorax. However, it has long been unclear whether BMI or height are causally associated with pneumothorax. Methods Genetic summary data for BMI, height and pneumothorax were retrieved from multiple independent large genome-wide association studies (GWAS). A series of quality control steps were conducted to select instruments. Four independent two-sample Mendelian randomization (MR) analyzes were performed to adequately assess the causal relationship between BMI or height on pneumothorax, and the robustness of the results was assessed by a series of sensitivity analyzes. Results Height increased the risk of pneumothorax with an OR of 1.5181 (95%CI 1.3092–1.7604; p = 3.28e-08); there was no evidence of a causal effect of BMI on the risk of pneumothorax with an OR of 0.8979 (95%CI 0.7417–1.0869; p = 0.269). Height increased the risk of spontaneous pneumothorax with an OR of 1.0010 (95%CI 1.0002–1.0018; p = 0.012); the results showed no significant causal relationship between BMI and spontaneous pneumothorax either with an OR of 0.9992 (95%CI 0.9983–1.0002; p = 0.112). Conclusion Our results supported a genetic association between height and pneumothorax. We found that height increased the risk of pneumothorax. However, no evidence was found to suggest a causal relationship between BMI and pneumothorax risk. The relationship between BMI and pneumothorax requires further in-depth analysis.